Pengaruh Tingkat Literasi Keuangan Terhadap Kinerja Pengelolaan Keuangan pada Koperasi Simpan Pinjam di Kabupaten Buleleng - Komang Gita Asri Utami; Ari Surya Dharmawan (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study was conducted with the aim to determine the effect of the level of financial literacy on the performance of financial management in Savings and Credit Cooperatives in Buleleng Regency. This research is a quantitative study,pwhere the data used in this study are primary data where primary data is collected through questionnaires and measurement techniques used are Likert scale techniques. This research was carried out in Buleleng Regency. Theesampling technique in this study is the purposive sampling technique, so that a sample of 50 KSP is obtained and 3 people are selected in the financial department as respondents so that 150 management and savings and loan collectors are obtained. The data obtained will be analyzed using several data analysis techniques with statistical tests usingg the SPSS version 23.0 computer program, namely: descriptive statistical tests, instrument quality tests, classic assumption tests, hypothesis tests,aand coefficient of determination tests (R2). After conducting various statistical tests and hypothesis testing with the t statistical test, the results of the hypothesis test show that the knowledge variable (X1) has a positive and significant effect on financial management performance on KSP, the understanding variable (X2) has a positive and significant effect on management performance finance on KSP, and the application variable (X3) has a positive and significant effect on financial management performance on KSP.